Improvement of additional education withthe account forprofilization of schools - S.V. Epifantsev (Язык и текст, 2017)
The article considers the growing urgency of the problem of profile teaching, which assumes further study of the issues of the allocation of organizational and pedagogical conditions for its effective implementation in the educational process, the development of flexible technological models and pedagogical strategies for the gradual transition from profile education to vocational education of students.